Agreement between endoscopic ultrasound-guided fine-needle aspiration and endobiliary brush cytology in suspected pancreaticobiliary malignancies - Sullivan, Matthew J.; Kincaid, Hope; Shah, Shashin; Shah, Hiral N. (Endoscopy International Open, 2017)
Background and study aims For suspected pancreaticobiliary malignancies, endobiliary brush cytology during endoscopic retrograde cholangiopancreatography (ERCP) remains the diagnostic test of choice despite historically poor and variable sensitivity. This has led to increased use of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) as an initial test. Recently, our institution began using a cytology brush that was designed specifically to collect a more substantial and higher-quality sample. The aim of this study was to investigate whether this brush design would provide more adequate samples and have high agreement with EUS-FNA in patients who underwent both procedures.Patients and methods A retrospective chart review was conducted of all patients who underwent both EUS-FNA and endobiliary brush cytology for suspicion of pancreaticobiliary malignancy from January 2013 to May 2015. A total of 41 patients met the inclusion criteria. Initially, sample quality was evaluated. Final cytology results were then assessed for agreement with EUS-FNA using Cohen’s kappa. The effect of considering atypical cytology as negative was also uniquely evaluated by running separate analyses.Results Brush cytology provided an adequate sample in 95.1 % of cases. Cohen’s Kappa demonstrated moderate agreement between brush cytology and EUS-FNA: κ = 0.42 (P = 0.001). When atypical results were excluded, agreement increased: κ = 0.60 (P = 0.02), but remained moderate. If atypical results were considered “positive,” the two procedures demonstrated equal cancer detection rates of 80.8 %.Conclusions The studied brush provided more adequate samples compared with historical rates for brush cytology and had moderate agreement with EUS-FNA. If this brush truly increases sample adequacy, it could potentially provide results comparable to EUS-FNA at lower cost.